On the motion of a viscous liquid with a free boundary - V. L. Sennitskii (Учёные записки Казанского университета: Серия Физико-математические науки)
The problem of the non-stationary flow of a viscous liquid with an external free boundary around a moving solid cylindrical body was formulated and solved. The liquid is subject to periodic impacts with or without the predominant direction in space. To formulate the problem, the Navier—Stokes equation, the continuity equation, and the equation of conditions at both the solid and free boundaries of the liquid were used. New hydro-mechanical effects were discovered.